The relationship between a delivery driver and a delivery app: Arguments of an employment relationship - Torres Cadillo, Rosa Isabel (2021)
The emergence of digital platforms brought substantial changes in the global economy, and with them a legal challenge to the new atypical work modalities, where the employers are not the same traditional employers ones, but applications such as Uber, Glovo, Cabify, Rappi, etc. In this regard, in our country, several bills sought to regulate the link between the service provided and the digital platform, under the figure of an employment relationship. However, it is the owners of these digital sites who reject their status as employers, defining themselves as intermediaries between service providers and their clients, intending to evade labor rights. Therefore, the question arises: «Is a Rappi or Glovo delivery person an employee of the company?». We consider that he/she is since he/she is subordinate and remunerated.